Heuristic “Bottom-up”: COVID-19 - Taranjeet Duggal1 , Ayush Sundriyal2, Abhishek Kakkar2 , Neeti Mittal2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: COVID 19, a global pandemic has led to the disruption all over the world. Not only theCOVID outbreak but the measures taken to straighten the curve led to the psychological distress amongstpeople. The disruption in daily routine which changed People’s lifestyle, the changed business workingenvironment while COVID and post COVID. The concept to adapt to the new normal still seems abrupt.Method: This present study was done amongst Indian youth and working professionals (age 18-28) inorder to understand their psychological well-being in these COVID times. With collection of data throughan online questionnaire more than 350 people participated. The instrument used was DASS-21 and a selfconceptualized VIRUS scale. All statistical analysis was computed through SPSS 21.Conclusion: This paper aims to contribute through exploration into the stressors and how the COVID situationhas brought about vexation, immediate concern, routine disruption and uncertainty about future. Throughthese four factors we obtain results that elaborates on what will affect their life’s the most, highlighting theneed for post-COVID interventional strategies in business environments and in one’s lifestyle.